Outcome of Inferior Pole Patellar Fractures Treated by Surgical Excision (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To determine the effectiveness of excision of distal pole of patella in functional and rate of infection parameters.Methods: An observational study was conducted from June 2012 to May 2014. Minimum of 10 patients of fractures of inferior pole of patella over the period of two years has been included in this study. All the patients with close fractures of inferior pole of patella of either sex in the age between 18-50 years were included in this study. All the fractures were treated by resection of the avulsed fragment. Results: Overall average mean of age was 38.40 with SD±13.30 years of 10 patients. Out of 10 patients, 08 were male and 02 were female. From 1st month till 6th months follow up time period none of the patients developed surgical site infection. Functional status at 6th month showed that 6 patients had excellent and four patients had good outcome.Conclusion: It is concluded that excision of the distal pole is a better option in comminuted fractures that are not amenable by fixation. To further enhance this treatment method long-term studies are required.Key Words: Patella fractures – internal fixation – excision.